Biological control of gastrointestinal nematodes of goats in semiarid climate by Monacrosporium thaumasium - Araújo, Jackson Victor de; Rodrigues, Maria de Lurdes de Azevedo; Silva, Wilson Wouflan; Vieira, Luiz da Silva (Pesquisa Agropecuaria Brasileira, 2007)
The present study aimed to evaluate the viability of the nematophagous fungus Monacrosporium thaumasium in the control of gastrointestinal nematodes larvae of goats in the field, in semiarid climate in Ceará State, Brazil. An area of 20 ha, free of worms, was divided into four paddocks of 5 ha. In each paddock, one group consisting of nine goats was formed and received the following treatment, individually, from April to June 2002: group 1, each animal received, orally, 10 g of pellets, weekly; group 2, the animals received 10 g of pellets, each 15 days; group 3, the animals received 0.5 mL moxidectin per 25 kg of live weight; group 4, control, not treated. Monthly, two tracer goats were introduced into the flock per 30 days. After this period, they were sacrificed and submitted to necropsy. The group of animals that received fungi treatments weekly showed reduction in the number of eggs per gram of feces, smaller parasitic load and larger weight in relation to animals of the other groups. The fungi M. thaumasium was efficient to control infective larvae in the pasture, and can be used in the control and prophylaxis of gastrointestinal nematodes of goats in semiarid climate, in Ceará State.